The Role of State on Social Justice: An Analysis from Ibn Sina’s Perpective - Ismail, Nurizal; Cahyo, Eko Nur (University of Darusssalam Gontor, 2018)
Every nation attempts to provide welfare for its citizen such as better economic growth,social security and better life. All economic systems either Capitalism or Socialism has thesame objective to provide welfare for its nation. In Islam, welfare lies in complete justice,mercy, welfare, and wisdom; anything that departs from justice to injustice, from mercyto harshness, from welfare to misery and from wisdom to folly has nothing to do with theShari’ah. The Islamic concept and values on welfare of the society are related to Islamiceconomic history that can be found from Qur’an and Sunnah and Islamic literatures suchas history, fiqh, philosophy, kalam, and tasawwuf. it is assumed that there are some Muslimscholars whose works are related to role of state on welfare. Therefore, the study attempts toknow the role of state on social justice derived from Ibn Sina and give some critical study onhis thought. To achieve its objectives; this study employs qualitative research that refers tothe meanings, concepts, definitions, characteristics, metaphors, symbols and descriptions ofthe matter understudy. Moreover, it is used content and descriptive analysis to get findingof the study. The data collection is generated from Islamic sources. The finding of this studyis that Ibn Sina’s thought on state role to promote social justice containts of providing law,job opportunities and social security. These roles of state can contribute to harmony, peaceand welfare of the society.